Prevalence Of Ocular Morbidities Among School Children: A Comparative Study Across Social Categories in Ajmer City - Bedi, Renu; Bedi, Dinesh Kumar; Dudule, Charushila N; Nizamuddin; Keswani, Mahesh; Saxena, Prabha (National Journal of Community Medicine, 2016)
Introduction: School children constitute a particular vulnerable group for ocular morbidities which can have has detrimental effect on the academic, social and later the functional potential of individuals. This study was conducted to determine the comparative prevalence of category wise distribution of common ocular morbidities and their demographic correlates. Methods: Descriptive cross sectional study done in J.L.N. Medical College and Hospital, Ajmer. STUDY PERIOD: October 2012 to September 2013. Results: 2754 study subjects comprised the sample. In our study category wise distribution of refractive error showed that there was descending order of percentage of student of refractive error was in general, OBC, SC, ST category students in all types of refractive errors i.e. myopia, astigmatism and hypermetropia. Conclusion: Reserved categories showed high ocular morbidity in total as compared to general unreserved category amongst the studied social categories.